Impact of Sharia Tourism Development in Pringsewu Regency Lampung - Basrawi Basrowi; Fauzi Fauzi; Pertiwi Utami (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
The purpose of this study was to describe the opportunities for sharia tourism in Pringsewu Regency by referring to the Law and Fatwa of the National Sharia Council. The research method used is empirical legal research which aims to support the development of legal science, especially sharia law related to halal tourism. Data is collected through documented observation. Examination of the validity of the data by using data source triangulation techniques is done by comparing the results of observational data with the results of related documents, and data analysis through data reduction, data presentation and conclusion drawing. Based on the results of the study concluded, 1) sharia tourism is very possible to be developed in Lampung Province, because formal juridical is not at all contradictory and Law No.33 of 2013 concerning Guaranteed Halal Products; 2) also does not contradict the Fatwa of the National Sharia Council-Indonesian Ulema Council No.108 / DSN-MUI / X / 2016 towards the development of sharia tourism.